MODERN PRACTICE OF REGULATING PROCESSES OF ATTRACTING FOREIGN INVESTMENTS AND APPROACHES TO ITS IMPROVEMENT - AZIMOVA HULKAR EGAMBERDIYEVNA; HASANOVA YULDUZ MURTAZAYEVNA; ESHEV ALIBEK SABIROVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
Investing plays a key role in fundamental economic processes taking place at the national, regional and microeconomic levels. The socio-economic potential of the region, the prospects for its development and use, and, accordingly, the improvement of the living standards of the population depend on the qualitative and quantitative characteristics of investments. Attracting foreign investment in the economy of the region is able to provide a new quality of productionthrough the use of advanced foreign technologies, advanced equipment, and the experience of modern management.